Effect of Different Height of Earthing up on Yield Performance of Groundnut under Irrigated Condition in Kilinochchi District, Sri Lanka. - Ragulan, G.; Nishanthan, S.; Pradheeban, L.; Sivachandiran, K. (World Journal phamaceutical and Life Science. 2(4): 471-481., 2016)
Research was conducted in Kilinochchi District to study the effect of different heights of earthing up on yield performance of groundnut during February to May 2016. Four different earthing up heights such as 0 cm, 5 cm, 10 cm, and 15 cm of groundnut (Tissa) was tested in RCBD with three replicates. The yield components of groundnut were recorded and data were analyzed in SAS. The yield components of groundnut among treatments were not significantly different except in shelling percentage and 100 pods weight. Earthing up treatment was not significantly influence on biomass increment ie there was no quantity changes observed while practicing earthing up. But quality improvement was observed in ground nut cultivation. The shelling percentage and 100 pods weight was increased due to earthing up treatments. The highest shelling percentage and 100 pods weight were observed at earthing up height of 5cm. Even though cost involved in the earthing up practice, cost incurred for earthing up of 5 cm height was not significant compared to other heights of earthing up. But yield of ground nut was increased at 5cm height of earthing up due to losses were avoided caused by vertebrates like birds and squirrels compared to no earthing up. Therefore, earthing up to the height of 5 cm gave bonus yield to farmers. It can be concluded that in ground nut cultivation, earthing up management practice is not compulsory for the cultivation but it enhanced the yield and gave additional income to farmers
Keywords: Earthing up; Groundnut; Income; Shelling percentage; Yield